Masses in right side of the heart: spectrum of imaging findings - Pradella, Silvia; Grazzini, Giulia; Letteriello, Mayla; De Amicis, Cristian; Grassi, Roberta; Maggialetti, Nicola; Carbone, Mattia; Carotti, Marina; Di Cesare, Ernesto; Giovagnoni, Andrea; Cozzi, Diletta; Miele, Vittorio (Acta Biomedica Atenei Parmensis, 2020)
Primary heart tumors are rare, benign tumors represent the majority of these. If a cardiac mass is found, the probability that it is a metastasis or a so-called “pseudo-mass” is extremely higher than a primary tumor. The detection of a heart mass during a transthoracic echocardiography (TE) is often unexpected. The TE assessment can be difficult, particularly if the mass is located at the level of the right chambers. Cardiac Computed Tomography (CCT) can be useful in anatomical evaluation and Cardiac Magnetic Resonance (CMR) for masses characterization as well. We provide an overview of right cardiac masses and their imaging futures.